2018
DOI: 10.3393/ac.2017.09.26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraoperative Insufflation With Warmed, Humidified CO2 during Abdominal Surgery: A Review

Abstract: PurposeDuring a laparotomy, the peritoneum is exposed to the cold, dry ambient air of the operating room (20℃, 0%–5% relative humidity). The aim of this review is to determine whether the use of humidified and/or warmed CO2 in the intraperitoneal environment during open or laparoscopic operations influences postoperative outcomes.MethodsA review was performed in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The PubMed, OVID MEDLINE, Cochrane Central Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Human and animal studies have found discrepant results regarding the effect of warmed, humidified carbon dioxide on peritoneal inflammation 30 . In laparoscopic human studies, it was reported 31 that peritoneal damage was less with the use of warmed, humidified carbon dioxide gas insufflation, but another study 32 documented no difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human and animal studies have found discrepant results regarding the effect of warmed, humidified carbon dioxide on peritoneal inflammation 30 . In laparoscopic human studies, it was reported 31 that peritoneal damage was less with the use of warmed, humidified carbon dioxide gas insufflation, but another study 32 documented no difference.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a tightly controlled process with factors that are proinflammatory and anti-inflammatory working simultaneously 30 . Whether localized peritoneal damage will promote a cascade of inflammation to the remaining bowel peritoneum is unclear; however, studies have shown that peritoneal damage is a feature occurring in animals and humans undergoing laparoscopy/laparotomy 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of both CL and SIL in the emergency setting appears safe and feasible, making a laparoscopy-first approach viable [24]. Strategies to further reduce adhesions during laparoscopic surgery may include the insufflation of warmed and humidified carbon dioxide, a technique which we did not use over the time frame of this study [25]. Two systematic reviews have examined the value of laparoscopic techniques for RoH [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…17 During a conventional laparoscopy, the peritoneum is exposed to the cold, dry ambient air of the operating theatre (20°C, 0%-5% relative humidity), which causes serious peritoneal damage. 17,58 Peng investigated the effect of hyperthermic CO 2 insufflation and humidified CO 2 insufflation on the development of peritoneal dissemination. 59 In their study, mice were divided into two groups and subjected to hyperthermic CO 2 insufflation (43°C, >95% humidity, HT-CO 2 group) or standard normothermic CO 2 insufflation (21°C, <1% relative humidity, NTCO 2 group) for 3 h. Peritoneal dissemination was evaluated quantitatively, and port sites and ascites were observed.…”
Section: Pneumoperitoneum Modificationmentioning
confidence: 99%
“…16 New concepts and methods for PSM prevention have appeared in recent years. 17 We reviewed the hypotheses of PSM pathogeneses in gynecologic oncology. In this way, we wished to summarize the progress in PSM prevention and to select the potential preventive options for patients with gynecologic malignancies.…”
Section: Introductionmentioning
confidence: 99%